Proceedings of the 4th International Conference on Higher Education Advances (HEAd'18) 2018
DOI: 10.4995/head18.2018.8093
|View full text |Cite
|
Sign up to set email alerts
|

Flipped Classroom at the Defence University

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…literature for the current research and with the results of many earlier researchers (Clyde & Nancy 2013;Crouch & Mazur 2001; De los 2014; Gecu and Satici 2012;Gerstein 2012;Jeremy 2007;Juhary 2015;Kurt 2017;Lim et al 2014). (2) Technological innovations were used in the study, and the students received feedback quickly at all times to know the extent of their progress and where they had reached.…”
supporting
confidence: 62%
“…literature for the current research and with the results of many earlier researchers (Clyde & Nancy 2013;Crouch & Mazur 2001; De los 2014; Gecu and Satici 2012;Gerstein 2012;Jeremy 2007;Juhary 2015;Kurt 2017;Lim et al 2014). (2) Technological innovations were used in the study, and the students received feedback quickly at all times to know the extent of their progress and where they had reached.…”
supporting
confidence: 62%
“…Based on the analysis, articles were categorised and ranked based on their frequency. Table 2 shows that out of nineteen articles, twelve were done with undergraduate students (Raman et al, 2019); ; ; (Sambandamurthi, 2015); (Techanamurthy et al, 2015); (Pudin, 2017); (Danker, 2015); (Tazijan et al, 2016); (Chew et al, 2018); (Juhary & Amir, 2017); (Abdullah & Azizan, 2018). The second largest group surveyed were the elementary school students and lecturers with two papers for each level done by Chun and Sathappan (2018) Table-3 Qualitative 1 Chew et al (2018).…”
Section: Resultsmentioning
confidence: 99%
“…While collaboration is a crucial component in flipped learning, students may struggle individually on standardized tests (Springen, 2013). Halili, Razak, and Zainuddin (2014) Flipped classroom approach for preschool students in learning English language 18 Juhary and Amir (2017) Flipped Classroom at the Defence University 19 Abdullah and Azizan (2018) A Flipped Classroom Technique in Improving Students' Grade of Transport Phenomena Course…”
Section: Disadvantages Of Flipped Learningmentioning
confidence: 99%
“…2016Peter, Laurel & Alan, 2016;Bulfin, Pangrazio and Selwyn, 2014;Fox, 2014;Chauhan, 2014). In Malaysia, previous research indicated very few studies have investigated the FC approach and most of the FC studies focus on higher education institutions Johary, 2015;Osman, Jamaludin & Mokhtar, 2014;Rozhan, 2015). Not much research that focuses on the use of FC for the learning community had been reported.…”
Section: Introductionmentioning
confidence: 99%